PERBEDAAN TINGKAT PENGETAHUAN TENTANG KESEHATAN REPRODUKSI SEBELUM DAN SESUDAH PEMBERIAN PENYULUHAN KESEHATAN MENGGUNAKAN MEDIA VIDEO PADA SISWA SMP NEGERI 3 TOMOHON - Tiara Christin Kayadoe; Prycilia Pingkan Mamuaja; Lucyana Pongoh (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Knowledge about reproductive health is an important aspect in adolescent development, because it influences their behavior related to sexual and reproductive health and helps prevent sexually transmitted diseases, teenage pregnancy, and other health problems. Therefore, education is needed for students, one of which is by conducting counseling using video media. The purpose of this study was to determine the difference in the level of knowledge about reproductive health before and after providing health counseling using video media to students of SMP Negeri 3 Tomohon. This type of research is experimental with a One-Group Pretest-Posttest Design. The sample used in this study was 71 students. The data collection technique used a questionnaire. Based on the research conducted, it was found that there was a difference in the level of knowledge about reproductive health before and after providing health counseling using video media. Most respondents before being given counseling had poor knowledge, namely 55 people (77.5%) and most respondents after being given had good knowledge, namely 63 people (88.7%). The p value is 0.000 <0.05